Understanding ForteBio’s Sensors for High-Throughput Kinetic and Epitope Screening for Purified Antibodies and Yeast Culture Supernatant - Yu, Yao (J Biomol Screen, 2016)
Real-time and label-free antibody screening systems are becoming more popular because of the increasing output of purified antibodies and antibody supernatant from many antibody discovery platforms. However, the properties of the biosensor can greatly affect the kinetic and epitope binning results generated by these label-free screening systems. ForteBio human-specific ProA, anti-human IgG quantitation (AHQ), anti-human Fc capture (AHC) sensors, and custom biotinylated-anti-human Fc capture (b-AHFc) sensors were evaluated in terms of loading ability, regeneration, kinetic characterization, and epitope binning with both purified IgG and IgG supernatant. AHC sensors proved unreliable for kinetic or binning assays at times, whereas AHQ sensors showed poor loading and regeneration abilities. ProA sensors worked well with both purified IgG and IgG supernatant. However, the interaction between ProA sensors and the Fab region of the IgG with VH3 germline limited the application of ProA sensors, especially in the epitope binning experiment. In an attempt to generate a biosensor type that would be compatible with a variety of germlines and sample types, we found that the custom b-AHFc sensors appeared to be robust working with both purified IgG and IgG supernatant, with little evidence of sensor-related artifacts.